Comparison of ultrasound-guided high-intensity focused ultrasound ablation and hysteroscopic myomectomy for submucosal fibroids: a retrospective study. (1st January 2021) - Li, Waixing; Yang, Zhipeng; Gao, Bingsi; Zou, Lingxiao; Xu, Dabao; Liu, Lu; Gu, Pan; Deng, Xinliang
Abstract: Objective: To compare the safety, reintervention and pregnancy outcomes between ultrasound-guided high intensity focused ultrasound (USgHIFU) and hysteroscopic myomectomy (HM) for submucosal fibroids. Materials and methods: A total of 215 patients with a solitary submucosal fibroid treated by USgHIFU or HM at the third Xiangya Hospital were retrospectively reviewed. Among them, 58 treated with USgHIFU, 157 treated with HM. Results: A significant difference was observed in size, location and type of the fibroids, effective rate, and cumulative reintervention rate between the two groups ( p < .05). The size of the fibroids was 57.9 ± 1.9 mm in the USgHIFU group, while it was 32.6 ± 1.2 mm in the HM group. The number of the fibroids at horn or fundus/uterine cavity was 16/42 in the USgHIFU group, while it was 21/136 in the HM group. The number of type I/II/2–5 was 16/17/25 in the USgHIFU group, while it was 133/24/0 in the HM group. In the USgHIFU group, the effective rate was 100% and the cumulative reintervention rate at 50 (17–97) months was 19.0%, while in the HM group, it was 94.3% and 7.6%, respectively. During the follow-up period, the pregnancy rate was 22.4% (13/58) and the reintervention rate due to invalid and recurrence was 15.5% (9/58) in the USgHIFU group, while they were 18.5% (29/157) and 7.0% (11/157) in the HM group. No significant difference was observed between the two groups ( p > .05). Furthermore, the reintervention rate was positively correlated with age, treatment methods and parity and fertility requirements. No other significant difference was observed between the two groups. Conclusions: Both USgHIFU and HM are safe and effective in treating submucosal fibroids. Compared with the HM group, the USgHIFU group had lower postoperative complications, but higher reintervention rate, with similar recurrence rate, pregnancy rate and reintervention rate due to invalid and recurrence. Reintervention was related to age, treatment methods, parity and fertility requirements.